Efficacy and Safety of Tropical Use of Tranexamic Acid during Off-Pump Coronary Artery Bypass Surgery: A Randomized Control Trial (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Postoperative mediastinal bleeding in patients undergoing cardiac surgery is still one of the most common complications.Objective: This study was intended to investigate the efficacy of topical tranexamic acid in reducing postoperative bleeding after post-operative cardiovascular surgery.Methodology: In this non-randomized, double blinded, clinical trial, patients undergoing Off-Pump Coronary Artery Bypass (OPCAB) surgery in NICVD, Dhaka, Bangladesh during January 2014 to December 2015 and fulfilling inclusion and exclusion criteria were recruited. They were assigned in two groups- 30 patients in tranexamic acid group (Group 1) and 30 patients in placebo group (Group 2). On completion of the grafting, before closure of the sternum tranexamic acid (2.5 g/25 mL) or placebo (25 mL of saline) diluted in 100 mL of warm saline (370 C) was instilled into the pericardial cavity including the mediastinal tissues and left for 5 minutes. Then it was cleared out by wall sucker and sternum was closed.Results: There was no significant difference in baseline demographic data, basic clinical characteristics and preoperative coagulation profile between the 2 groups (P > 0.05). Total mediastinal bleeding in group 1 and group 2 patients were421.67±70.32 vs 593.33±77.38ml, p